Mandatory but Unverified: A Socio-Legal Analysis of ESG Disclosure Decoupling under POJK 51/2017 and ASEAN-5 Regimes - Arya Ganendra; Grace Freya Purba; Firzan Dahlan (Enigma in Law, 2025)
Indonesian law makes corporate sustainability disclosure mandatory, yet doubt attends it: that firms produce the appearance of compliance, not its substance. This article turns that doubt into a legal question and a measurable test. Framed as empirical socio-legal research anchored in Article 74 of UU No. 40/2007 and POJK No. 51/POJK.03/2017, it distinguishes the breadth of what firms are legally induced to commit to from the depth to which commitments are verified, coding both from primary documents. A structured content analysis of the fiscal 2023–2024 sustainability reports of fifty large-cap firms — ten per ASEAN-5 market — scored fourteen binary indicators (six symbolic, eight substantive), with reliability confirmed by a blind second coder (Cohen's kappa 0.784). Symbolic commitment was near-saturated (mean 0.97) while substantive verification was uneven (0.74), producing a mean gap of +0.235; 78% of firms disclosed more than they verified. Decisively, the two dimensions were statistically independent (Spearman rho = 0.08, p = 0.57): the breadth of a firm's promises carried no information about their verification. The gap tracked regime maturity (Kruskal-Wallis p = 0.002), rising from Singapore (0.07) to the Philippines (0.41), and shrank under state ownership, but was unrelated to environmental exposure. The binding constraint on credible compliance is therefore the legal demand for verification, not corporate ambition. The article assesses Indonesia's regime de lege lata and proposes three de lege ferenda reforms — mandatory external assurance, prescribed Scope 1–3 reporting, and enforced comparability with graduated sanctions — grounded in the 1945 Constitution and ISSB convergence.